PENGARUH BIOFILTER SERAT BENANG DALAM MENURUNKAN PARAMETER pH, BOD, COD DAN TSS TERHADAP LIMBAH CAIR TEKSTIL DI PT ARGO PANTES TBK, TANGERANG - Rizka Afriani (JURNAL TECHLINK, 2019)
PT Argo Pantes Tbk. Tangerang as a textile factory in the city of Tangerang seeks to manage the waste it produces by processing wastewater that is released into a waste treatment plant, the Waste Water Treatment Plant (IPAL) using a fiber-fiber biofilter media which is a by-product from the production of PT Argo Pantes Tbk. The purpose of this study was to determine the performance of biofilter in treating textile liquid waste against pH, COD, BOD and TSS values. Knowing the performance of an effective type of starter for treating textile liquid waste against pH, COD, BOD, and TSS values. Knowing the optimum residence time to treat textile wastewater with biofilter and the pH, COD, BOD, and TSS values. This research was conducted using a variety of starter types, namely Pseudomonas sp and EM4 and a residence time of 48 hours and 72 hours. The results of studies with the use of starter EM4 are better than and can reduce COD values up to 65-105 mg / L or 91.8% -95.6% of influent, BOD up to 49.46-89.95 mg / L or 88.7% -93.7% of influent, TSS to be 11.73-17.02 mg / L or 88.5% -91.8% of influent and the pH value has increased to 7.28-7.45 or 5.9% -8.8% of influenza. From the results of the study it was found that a residence time of 72 hours was better than 48 hours in reducing COD, BOD and TSS.